Conference Report: Boston Society's 7th Applied Pharmaceutical Analysis. (January 2012) - Kumar, G; Weiner, R; Vick, A; Xia, C; Dalvie, D; Bateman, K; Ramanathan, R
The Boston Society hosted the 7th Applied Pharmaceutical Analysis (APA) conference in Cambridge (MA, USA) from September 12th to 14th 2011. The overarching theme for this year's meeting was 'Smaller and Smarter' covering a variety of topics on how qualitative and quantitative analysts are creatively using novel and emerging techniques to improve analytical sensitivity, which affords the use of smaller sample volumes while striving to meet the ever-increasing regulatory expectations, as well as cost, resource and time constraints.